2003
DOI: 10.1002/hyp.1195
|View full text |Cite
|
Sign up to set email alerts
|

Importance of soil surface characteristics on water erosion in a small grazed Sahelian catchment

Abstract: Abstract:This study concerns the problem of water erosion in the Sahel. Surface water and sediment yields (suspended matter and bedload) were monitored for 3 years (1998)(1999)(2000) at the outlet of a small grazed catchment (1Ð4 ha) in the northern part of Burkina Faso. The catchment consists of about 64% sandy deposits (DRY soil surface type), which support most of the vegetation, and about 34% of crusted bare soils (ERO soil surface type). The annual solid-matter export is more than 90% suspended sediment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 9 publications
1
33
0
Order By: Relevance
“…There is a tendency for ERO crusts to develop in clayey soil horizons, DES and STRU to develop under sandy soil conditions and for GRAV crusts to form under the coarsest soil textures (Casenave and Valentin, 1989). Several studies (de Rouw and Rajot, 2004;Graef and Stahr, 2000;Karambiri et al, 2003;Malam-Issa et al, 2011) in the Sahel supplied information on impacts of soil crusting on infiltration and soil erosion, yet, little is known about the impacts of soil crusting on SOC losses.…”
Section: Introductionmentioning
confidence: 99%
“…There is a tendency for ERO crusts to develop in clayey soil horizons, DES and STRU to develop under sandy soil conditions and for GRAV crusts to form under the coarsest soil textures (Casenave and Valentin, 1989). Several studies (de Rouw and Rajot, 2004;Graef and Stahr, 2000;Karambiri et al, 2003;Malam-Issa et al, 2011) in the Sahel supplied information on impacts of soil crusting on infiltration and soil erosion, yet, little is known about the impacts of soil crusting on SOC losses.…”
Section: Introductionmentioning
confidence: 99%
“…Their results emphasise the necessity to take into account both wind and water erosion processes to assess the actual land degradation in the Sahel. Furthermore, Rajot et al (2002) and Karambiri et al (2003) have shown that the surface characteristics determine mainly the pattern of erosion and deposition of sediment in a small-scale catchment. This emphasises the need for more research on wind and water erosion at a larger (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…For the Niger Republic during the 1999-2006 period, Garba [38] observed a decrease in biomass in a study based on NDVI; but he explains this by the fact that the year 1999-2000 was a humid one. Karambiri et al [39], Diello et al [40] and Hauchart [41] also noticed a reduction in vegetation cover in two different regions of Burkina Faso (the Nakambe and Mouhoun basins). Lié nou et al [42] made similar observations in Cameroon, which are consistent with the works of Amani and Nguetora [9], and Mahé et al [43] on the west bank of the Niger River.…”
mentioning
confidence: 98%